Research progress on the role of dendritic cells in glioma during 1992-2024: a bibliometric analysis - Zhu, Linglei; Zhang, Linpeng; Han, Shuqi; Zhou, Xuan; Pan, Hai; Li, Fanghe; Gao, Kuo (Frontiers in Immunology, 2025)
BackgroundGliomas represent the most prevalent primary neoplasms of the central nervous system. Activating an immune response by dendritic cells is pivotal in glioma immunotherapy. This study offers a comprehensive bibliometric analysis to elucidate the role of dendritic cells in gliomas.MethodWe extracted literature related to glioma and dendritic cells from 1992 to 2024 using the Web of Science Core Collection. Utilizing CiteSpace, Vosviewer and Microsoft Excel, we analyzed the volume of publications, the contributing countries/regions, institutions, authors, journals, references and keywords.ResultsA total of 1,576 articles were included, revealing an annual surge in dendritic cell-focused glioma research. The USA, China and Germany were the leading countries in publication output. Okada, Hideho had the most publications, while Stupp, R had the highest co-citations. Journal of Neuro-Oncology published the most articles, and Cancer Research received the highest citations. The analysis highlights pivotal themes including “dendritic cell”, “immunotherapy”, and “glioblastoma”, alongside emerging areas of interest such as “tumor microenvironment”, “immune infiltration” and “double blind”. Notably, the exploration of dendritic cell vaccinations is a key area of glioma therapeutic research, and there is growing interest in it.ConclusionThis study conducts a bibliometric analysis of publications related to dendric cells in glioma. Our findings suggest that dendritic cells, immunotherapy and glioblastoma will remain the focal points and emerging trends in dendritic cell-glioma research, providing valuable insights for future studies. Dendritic cell vaccines show promise in glioma trials but are hindered by the immunosuppressive tumor microenvironment. Future work should enhance dendritic cell function and explore combination therapies to improve outcomes.